Perancangan dan Implementasi Website Pemesanan Makanan FOODHUB Berbasis Web - Dewi, I Gusti Ayu Nirmala; Gayatri, Anak Agung Rai; Purnajayanti, Komang Restisya; Sanjaya, I Gede Wahyu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The development of digital technology today has driven significant changes in people's consumption patterns, including in the food and beverage industry. However, many Micro, Small, and Medium Enterprises in the culinary sector still rely on traditional methods or social media that are not designed for commercial transactions, resulting in various problems that occur, such as in recording and managing orders. This study aims to design and implement FoodHub, a website-based food ordering site that is intended to help digitize the culinary Micro, Small, and Medium Enterprise business process. The system was developed using the prototyping method, with PHP Native, MySQL technology, as well as HTML, CSS, and JavaScript on the user interface. The main features include category pages, product pages, product detail pages, and others. Based on the results of system testing using the BlackBox Testing method, 100% valid results were obtained. Referring to these results, the system is running according to user needs and is declared feasible to be operated by Micro, Small, and Medium Enterprises effectively and efficiently.